Examining the Securitization of Muslim Immigrants in France Under the Anti-Separatist Act of President Emmanuel Macron - Astira, Meylan Zhara (JLAST : Journal of Law and Social Transformation, 2023)
The entrance of Muslim immigrants in France in search of employment gave rise to the problem of Muslim immigration in France. The French government initially welcomed the entrance of Muslim immigrants because it required laborers to complete post-war reconstruction. Due to the growing immigrant Muslim population, these individuals have gathered, constructed mosques, established Islamic organizations, and formed groupings. increasing the visibility of Muslim identity. This is viewed as an outsized challenge to Islamic ideology in terms of French secularist philosophy. The attack on the WTO building, which worsened the already negative perception of Muslims, made this situation worse. In addition, President Macron manipulates the debate over Muslim immigration to further his political agenda. Macron enacted anti-separatist laws and anti-immigrant policies, which further marginalized Muslim immigrants. Macron became a securitization actor and actively declared that Islam was a radical, terrorist, and separatist religion to further his interests. The overwhelmingly Islamophobic French society endorses Macron's remarks. Thus, by embracing Macron's proposal, the problem of Muslim immigration has reached the securitized point, at which point the government must address the problem by enacting anti-separatist legislation.